2020
DOI: 10.3389/fonc.2020.515421
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Prediction of Survival by a 10-Long Non-coding RNA-Based Prognostic Model for Patients With Breast Cancer

Abstract: Deregulations of long non-coding RNAs (lncRNAs) have been implicated in the progression of breast cancer (BC). However, the prognostic values of those lncRNAs in BC remain elusive. This study aimed at constructing a lncRNA-based prognostic model to improve the clinical management of BC. Systematic investigation of lncRNA expression profiles and clinical data from The Cancer Genome Atlas (TCGA) database were utilized to establish a 10-lncRNA signature. The prognostic signature efficiently discriminated patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…PCAT6 enhances proliferation and EMT in gastric cancer (GC) 29 , and KDM5B enhances EMT in lung cancer cell line, A549 30 , and in hepatocellular carcinoma 31 . LHX1 is involved in modulating EMT induction in uterine corpus endometrial carcinoma 32 , and LHX1-DT enhances cell proliferation in breast cancer 33 . These coordinated gene expression changes that were up-regulated by TGFβ stimulation were also confirmed by qRT-PCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PCAT6 enhances proliferation and EMT in gastric cancer (GC) 29 , and KDM5B enhances EMT in lung cancer cell line, A549 30 , and in hepatocellular carcinoma 31 . LHX1 is involved in modulating EMT induction in uterine corpus endometrial carcinoma 32 , and LHX1-DT enhances cell proliferation in breast cancer 33 . These coordinated gene expression changes that were up-regulated by TGFβ stimulation were also confirmed by qRT-PCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…About 20%–30% of breast cancer patients with early age will finally develop metastatic lesions (Early Breast Cancer Trialists' Collaborative G, 2005; Xie et al, 2019). For female patients, plenty of studies had investigated various markers to monitor disease change as to react timely (Huang, Hua, et al, 2020; Wang et al, 2020; Yang et al, 2020). However, there were a few researches about predictive model for metastatic male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are noncoding RNAs that are over 200 nucleotides in length and are attracting increasing attention due to their biological effects on a series of cellular processes by affecting gene expression via transcriptional, posttranscriptional, and epigenetic regulation 7 . Emerging reports have indicated that dysregulation of lncRNAs are involved in the occurrence, recurrence, and metastasis of BC 8 . For example, lncRNA H19 functioned as an oncogenic gene in BC by facilitating epithelial‐mesenchymal transition (EMT) invasion and migration by upregulating Snail lncRNA TTN‐AS1 was significantly overexpressed in the tissues and cells of triple‐negative BC in clinical tissues and cell lines, and its knockdown suppressed the proliferative, migratory, and invasive abilities of tumor cells 9 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Emerging reports have indicated that dysregulation of lncRNAs are involved in the occurrence, recurrence, and metastasis of BC. 8 For example, lncRNA H19 functioned as an oncogenic gene in BC by facilitating epithelial-mesenchymal transition (EMT) invasion and migration by upregulating Snail lncRNA TTN-AS1 was significantly overexpressed in the tissues and cells of triplenegative BC in clinical tissues and cell lines, and its knockdown suppressed the proliferative, migratory, and invasive abilities of tumor cells. 9 Cancer susceptibility candidate 9 (CASC9) was identified as a tumor-promoting lncRNA in several human cancers, such as esophageal cancer, lung adenocarcinoma, and BC.…”
mentioning
confidence: 99%